Book of abstracts of the 16th ITTF Sports Science Congress Budapest, 19th - 20th April 2019 (Sports and Health Sciences Notebooks, 2019)
Abstracts from the 16th ITTF Sport Science Congress in Budapest (2019, April 19-20) which was organised by the University of Pécs, Faculty of Health Sciences together with the Hungarian Table Tennis Association and the ITTF Sport Science and Medical Committee.